Isolasi Cendawan Endofit pada Daun Bambu Betung (Dendrocalamus asper Backer.) dan Potensi sebagai Antibakteri Staphylococcus aureus - Lydia Yohana Safitri (UNIVERSITAS NEGERI PADANG, 2017)
Endophytic fungi are microorganisms found in healthy plant tissue but not pathogenic to plants, and produce secondary metabolites same host plant. Secondary metabolites can be used as a drug. The possibility of endophytic fungi are found in bamboo, because bamboo betung (Dendrocalamus asper Backer.) Has high potential as a drug, because it contains flavonoids, and phenolic coumarin. These compounds are secondary metabolites that produce antimicrobial substances that are used in the pharmaceutical field and are found in plant tissue. To avoid excessive use of medicinal plants that could lead to the extinction of these plants, then used the role of endophytic fungi are capable of producing secondary metabolites to the fullest. In addition, the endophytic fungus in plant tissue can be more than one type of fungal endophyte that the higher production of secondary metabolites. This study aims to determine the types of isolates of endophytic fungi on the leaves of Dendrocalamus asper and know the antibacterial potency against bacterial endophyte fungus Staphylococcus aureus. The results showed that there were thirteen isolates of endophytic fungi were isolated from the leaves of Dendrocalamus asper. Ten isolates of endophytic fungi have potential as an antibacterial against S. aureus and three isolates of endophytic fungi did not show any antibacterial activity. Key Word: Endophytic fungi, Secondary metabolites, antibacterial activity.